Male mice treated with combined anti-fibrotic therapeutics, IPW5371 and tadalafil, are predisposed to adverse cardiovascular events - Stephens, Jazz Q.; Blas-Machado, Uriel; Sherrill, Chrissy; Caudell, David; Kock, Nancy; Davis, Ashley M.; Whitfield, Jordyn M.; Hart, Barry; Kavanagh, Kylie (Frontiers in Pharmacology, 2025)
Fibrosis is a pathological process with few therapeutic options. Experimental molecules are being developed to counteract the fibrotic effects through TGFβ receptor inhibition. Additionally, phosphodiesterase 5 (PDE5) inhibitors also have anti-fibrotic effects; however, the mechanism of action remains unresolved. IPW5371 is an example of an experimental TGFβ-mediated anti-fibrotic compound, and tadalafil is an example of a PDE5 inhibitor. Irradiation increases the frequency of fibrotic lesions, driven by the activation of the TGFβ pathway. We hypothesized that the TGFβ receptor and PDE5 inhibitor agents would be additive in their ability to prevent fibrosis development in tissues in a sub-lethal whole-body irradiation mouse model. However, the combined use of anti-fibrotic agents, tadalafil and IPW5371, caused increased male mouse mortality associated with ascending and thoracic aortic rupture compared to mice that only received one of the drugs. Following histopathological analysis of the mouse hearts, we also observed that irradiation protected against lesions caused by the combination therapy as non-irradiated male mice had significantly worse outcomes as compared to irradiated male mice, substantiating the drug–drug interaction independent of the radiation effects. This important drug interaction needs further investigation as these agents are developed for anti-fibrosis therapy, and PDE5 inhibitors are commonly prescribed to male patients.